2009
DOI: 10.1128/ec.00017-09
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Senescent Cryptococcus neoformans and Implications for Phenotypic Switching and Pathogenesis in Chronic Cryptococcosis

Abstract: Although several virulence factors and associated genes have been identified, the mechanisms that allow Cryptococcus neoformans to adapt during chronic infection and to persist in immunocompromised hosts remain poorly understood. Characterization of senescent cells of C. neoformans demonstrated that these cells exhibit a significantly enlarged cell body and capsule but still cross the blood-brain barrier. C. neoformans cells with advanced generational age are also more resistant to phagocytosis and killing by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
74
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(79 citation statements)
references
References 36 publications
5
74
0
Order By: Relevance
“…Standard in vitro phagocytosis indices, and macrophage killing assays were done in J774.16 cells as previously described. 24 IPR and laccase activity was determined as previously described. 15 For infection with Galleria mellonella, a 10 ml suspension of 2£10 4 , 10 5 , or 10 6 C. neoformans cells was used to infect larvae (n D 20) (Vanderhorst Wholesale, Inc., OH) in the last proleg as described previously.…”
mentioning
confidence: 99%
“…Standard in vitro phagocytosis indices, and macrophage killing assays were done in J774.16 cells as previously described. 24 IPR and laccase activity was determined as previously described. 15 For infection with Galleria mellonella, a 10 ml suspension of 2£10 4 , 10 5 , or 10 6 C. neoformans cells was used to infect larvae (n D 20) (Vanderhorst Wholesale, Inc., OH) in the last proleg as described previously.…”
mentioning
confidence: 99%
“…Chronological aging refers to the effects of time on a cell after it has stopped growing, whereas generational age refers to the number of daughter cells produced by a given cell. Fungal cellular aging may be important in the pathogenesis of cryptococcosis, since chronicity is associated with the persistence of cells in lung (21) and senescent cells have been shown to accumulate in the course of infection (25). Aging in C. neoformans produced capsule changes that were associated with resistance to phagocytosis by macrophages and antibody (Ab) reactivity.…”
mentioning
confidence: 99%
“…In this study, we investigated the effect of chronological aging under prolonged stationary-phase growth conditions on the dynamics of the PS capsule. We note that such aging in nondividing yeast cells (2) is a process fundamentally different from reproductive senescence, which has also been implicated in virulence and persistence for C. neoformans (25). Chronological aging refers to the effects of time on a cell after it has stopped growing, whereas generational age refers to the number of daughter cells produced by a given cell.…”
mentioning
confidence: 99%
“…Recent studies have begun to investigate the effects of age on C. neoformans cells to reveal other effects, like an increase in phenotypic switching frequency. 26 Nevertheless, most researchers use a standard overnight culture of cells grown in rich medium for starting inocula in experiments, a condition that is unlikely the wild or during infection are unknown, although there are candidate molecules for within the central nervous system and in the environment.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%
“…20 For melanin, the authors have previously shown that laccase is preformed in vesicles Further, an increase in phenotypic switching rates in aged cells could also provide better adaptability. 26 A prediction from these findings is that growth conditions may influence the outcome of an infection. This has been demonstrated independently, in other studies not focused on melanin, in which the culture conditions used prior to inoculating the cells into animals influences the rapidity of disease development.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%